1994
DOI: 10.1111/j.1467-7660.1994.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Conflict Between Growth and Welfarism? The Significance of the Sri Lanka Debate

Abstract: This article seeks to derive some general lessons regarding the relationship between growth and welfarism by undertaking a reassessment of Sri Lanka's long experience with interventions in social spheres. While Sri Lanka has been hailed by many for pursuing the welfarist strategy with apparently spectacular results, several critics have recently suggested that she would have been better off by diverting resources away from welfare interventions towards investment for growth. They have argued that the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Sociologists have suggested that the young have few support systems and are unable to cope with societal and cultural demands. 7 8 Frustrations felt by Sri Lanka's highly educated youth in the face of war, poverty, and the lack of opportunity at home and abroad are also likely to be exacerbating factors 9…”
Section: Deliberate Self Harm or Attempted Suicide?mentioning
confidence: 99%
“…Sociologists have suggested that the young have few support systems and are unable to cope with societal and cultural demands. 7 8 Frustrations felt by Sri Lanka's highly educated youth in the face of war, poverty, and the lack of opportunity at home and abroad are also likely to be exacerbating factors 9…”
Section: Deliberate Self Harm or Attempted Suicide?mentioning
confidence: 99%
“…It was concerned with social development indicators (or changes in these indicators) as measures of welfare standards of weaker groups in society (Bhalla, 1988a;Anand & Kanbur, 1991;Osmani, 1994). And it was seen in relative terms, re¯ected in Gini coef® cients that went beyond poverty alleviation as such to encompass distributional issues affecting the entire society (Glewwe, 1986(Glewwe, , 1988aRavallion & Jayasuriya, 1988).…”
Section: National Trends In Equity and Basic Needs Provisionmentioning
confidence: 99%
“…Perhaps the best re¯ection of this was in relation to education. Since the early 1970s, the orthodox view has been that there is a mismatch between educational achievements and employment opportunities (Osmani, 1994). Usually the assumption has been that the people with high educational achievements queue and wait for the lifetime security of public sector jobs (ILO, 1971).…”
Section: What Happened In Sri Lanka?mentioning
confidence: 99%
“…The public sector share of GDP had increased to around 15 percent by the mid-1970s from less than 6 percent in 1961 and it accounted for over 50 percent of employment and 60 percent of value added in the "organized" manufacturing sector by the late 1970s. 7 This had a particularly severe effect on the employment opportunities of Tamil youth because, as in many other countries in 6 Asian Economic Papers Economic Policy Shifts in Sri Lanka 5 For a useful review of this debate, see Osmani (1994). similar circumstances, political patronage had become a major factor in public sector employment.…”
Section: Background To the Ethnic Conºict And Separatist Warmentioning
confidence: 99%